Prevalence and temporal trends of physical activity counselling in primary health care in Germany from 1997–1999 to 2008–2011. Issue 1 (December 2015) - Gabrys, Lars; Jordan, Susanne; Schlaud, Martin
Abstract Background For patients, usually the first and most preferred contact person on health issues is still the doctor and most persons see their doctor at least once a year. Therefore, physical activity counselling strategies delivered by a physician seem to be a promising approach for physical activity improvement. The aim of this work is to show prevalence and time trends in physical activity counselling by primary health care physicians from 1997–1999 to 2008–2011 in Germany. Methods Data from two representative cross-sectional health interview and examination surveys of the Robert Koch Institute were used. Prevalence proportions of physicians' physical activity counselling and patients' utilisation of health promotion programmes in relation to physical activity counselling were analysed. Strengths of associations were calculated by using binary logistic regression models. Overall, 11, 907 persons aged 18–64 years were included in the analyses. Results Physical activity counselling prevalence decreased from 11.1 to 9.4 % in men and from 9.3 to 7.7 % in women over ten years. Only persons with accumulated health risks (OR 5.33; 95 % CI 1.89–15.00) and persons with diagnosed diabetes mellitus (OR 3.42; 95 % CI 1.68–6.69) showed significantly higher counselling proportions in 2008–2011 compared to 1997–1999. Men were more often counselled on physical activity than women, but women showed significantly higher participation rates in physical activity promotion programmes in both surveys. In both sexes significantly higher participation rates could be observed in persons who had received some activity counselling by a physician. Conclusion Although, evidence underlines the positive health effects of regular physical activity; overall, physicians counselling behaviour on physical activity decreased over time. However, it is positive to note that a trend towards a disease-specific counselling behaviour in terms of a tailored intervention could be observed.